THE ANALYSIS OF CONSUMER BASED BRAND EQUITY PERCEPTIONS ON THE BASE OF GSM OPERATORS: EXAMPLE OF VAN YUZUNCU YIL UNIVERSITY - Yusuf Cahit ÇUKACI (Fırat University, 2019)
The concepts of brand and brand equity have become concepts importance of which has been increasing day by day in today's changing and developing marketing conditions. Emerging to distinguish similar products and explained with any sign, term, symbol or some different forms, the concept of brand has much wider meaning now and became a means of expressing identity and value. The concept of brand equity which brand owns independent from the products has become one of the most discussed concepts for both financial point and value added that it provides to the consumer. The concept of consumer-based brand equity which is the main subject of this study began to take place in literature especially in the 1980s and later. This concept that is shortly defined as the equity consumers attributed to the brand consists of such components as brand awareness, brand loyalty, brand association and perceived quality. The main purpose of this study is to handle and measure brand equity with the consumer-based perspective. Within formed formats based on the consumer based brand equity model developed by David Aaker (1991) and Kevin Kane Keller (1993), it is aimed to fix brand equity perception of the University youth on the GSM operators that they use. Within this aim, a research was carried out by using survey method on 675 students studying at the Yuzuncu Yıl University.